Village clusters and rural development - Ramacandran, H.; Rao, V. K. R. V. (New Delhi Concept publishing company Pvt. Ltd., 2024)
In the field of integrated rural development the cluster approach has gained a lot of interest and importance in recent years. Village Clusters and Rural Development outlines the concept and its use in development planning. More importantly, it puts forward a definitive method of identifying clusters of villages that could form the unit area for micro-level planning.